Can neurophysiological markers of anticipation and attention predict ADHD severity and neurofeedback outcomes? - Aggensteiner, Pascal; Albrecht, Björn; Strehl, Ute; Wörz, Sonja; Ruckes, Christian Rainer; Freitag, Christine M.; Rothenberger, Aribert; Gevensleben, Holger; Millenet, Sabina; Hohmann, Sarah; Banaschewski, Tobias; Legenbauer, Tanja; et al. (Biological psychology, 2021)
Neurophysiological measures of preparation and attention are often atypical in ADHD. Still, replicated findings that these measures predict which patients improve after Neurofeedback (NF), reveal neurophysiological specificity, and reflect ADHD-severity are limited. - Methods - We analyzed children’s preparatory (CNV) and attentional (Cue-P3) brain activity and behavioral performance during a cued Continuous Performance Task (CPT) before and after slow cortical potential (SCP)-NF or semi-active control treatment (electromyogram biofeedback). Mixed-effects models were performed with 103 participants at baseline and 77 were assessed for pre-post comparisons focusing on clinical outcome prediction, specific neurophysiological effects of NF, and associations with ADHD-severity. - Results - Attentional and preparatory brain activity and performance were non-specifically reduced after treatment. Preparatory activity in the SCP-NF group increased with clinical improvement. Several performance and brain activity measures predicted non-specific treatment outcome. - Conclusion - Specific neurophysiological effects after SCP-NF were limited to increased neural preparation associated with improvement on ADHD-subscales, but several performance and neurophysiological measures of attention predicted treatment outcome and reflected symptom severity in ADHD. The results may help to optimize treatment.